Factores psicológicos para el rendimiento académico de los atletas del colegio de bachillerato “Pio Jaramillo Alvarado” del barrio San Sebastián, de la ciudad de Loja, durante el período académico 2013-2014 - Ordóñez Silva, Guido Sebastián (2015)
This research is aimed to know Psychological factors for the academic performance of college athletes’ baccalaureate "Pio Jaramillo Alvarado" of San Sebastián neighborhood of the city of Loja, during the academic 2013-2014. It starts from the marked object of study that is given by the Psychological Factors in Performance Athletes detected problematic situation, these factors have a significant impact on the performance of athletes in developing their physical abilities and intellectuals. The objective was aimed at establishing the psychological factors that affect the academic performance of college athletes baccalaureate "Pio Jaramillo Alvarado" of San Sebastián neighborhood of the city of Loja, during the academic 2013-2014. This research has three major categories such as: Psychological Factors, Academic Performance and athletics. The research has a qualitative approach with a type of longitudinal study and a pre experimental design based on the application of a pretest and posttest. The discussion then works and then analyzing the results is performed, concluding that psychological factors are impacting directly on the performance of athletes baccalaureate school "Pio Jaramillo Alvarado" of San Sebastian city neighborhood Loja. Taking as reference the results, is a recommendation of research: Continue studies in the area of psychological factors, relating it to their own athletes variables.